'A galaxy of sporting events': sport's role and significance in the Festival of Britain, 1951. Issue 4 (1st October 2016) - Wilton, Iain
ABSTRACT: The 1951 Festival of Britain has long been seen as a key moment in the country's post-war history – especially in terms of popularising modern architecture and contemporary interior design, as well as symbolising the transition from acute economic austerity to a long period of relative affluence. However, successive writers have largely or completely ignored sport's role in the Festival project. This paper argues that, in fact, sporting fixtures played an important role in the national and local festivities which were staged between May and September 1951. Their range, diversity and popularity means that the Festival should begin to be seen as a more successful and less insular event than previous studies have suggested. On the other hand, the support that such fixtures received from various newspapers and via the airwaves – courtesy of the BBC – indicates that the Festival faced far less media (and, indeed, political) opposition than its organisers liked to suggest and most historians have hitherto accepted. By studying the Festival's sports programme, therefore, it is possible to gain fresh insights into the project as a whole and reassess its overall performance.